The impact of the crisis triggered by the COVID-19 pandemic and the actions of regulators on the consumer finance market in Poland and other European Union countries - Łukasz Gębski (Risks, 2021)
The economic crisis triggered by the COVID-19 outbreak has severely affected the global economy. The ultimate scale of the recession is yet to be determined, but it is likely to be the most dramatic slump sinceWorldWar II. The impact of the crisis on the financial sector, especially consumer finance, could almost instantly be observed. The article shows how determination and consistency in regulatory actions counteracts the effects of the pandemic crisis for the banking sector and consumer finance. The conducted research has shown the existence of a number of social phenomena typical of this type of global crisis, such as shopping panic, reduced creditworthiness of households related to loss of income, unemployment and increased crime. At the same time, the actions of financial market regulators turned out to be very effective (no negative structural phenomena occurred in the financial market). The accuracy of the selection of instruments and the speed of action limited the social and financial effects of the pandemic, including a loan repayment memorandum, limiting the cost of consumer loans and supporting the banking sector, which will limit the scale of excessive household debt and consumer bankruptcies, and companies were also supported. The research was conducted on the basis of available literature on the subject, market analyses and a review of regulations implemented at the central level and in individual EU member states.
Keywords: 330; financial services; financial market regulation; consumer finance; COVID-19